A broadband array antenna using epsilon‐near‐zero metamaterials for MIMO applications. Issue 7 (1st September 2018) - Mazaheri, Mohammad. H.; Jafargholi, Amir
Abstract: In this article, the capability of epsilon‐near‐zero (ENZ) metamaterial (MTM) to reduce mutual coupling between densely packed array elements is examined. The results show a reduction in mutual coupling between antenna elements and provide a possible way to reduce the element separation. To verify and confirm the simulation results, a prototype of the proposed ENZ structure incorporating an array of closely implemented patch antennas, 0.12 λ L, are fabricated and tested. The array antenna has an overall dimension of approximately 2.66 λ L × 1.75 λ L × 0.05 λ L while achieving an average gain and efficiency of 7 dB and 85%, respectively. Measurement shows that the mutual coupling is mostly better than −20 dB across a broad bandwidth of >2.6:1 (10.5–27.7 GHz).